2015
DOI: 10.1128/jvi.00958-15
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of DNA Damage Signaling and Cell Death Responses by Epstein-Barr Virus Latent Membrane Protein 1 (LMP1) and LMP2A in Nasopharyngeal Carcinoma Cells

Abstract: Nasopharyngeal carcinoma (NPC) is closely associated with latent Epstein-Barr virus (EBV) infection. Although EBV infection of preneoplastic epithelial cells is not immortalizing, EBVcan modulate oncogenic and cell death mechanisms. The viral latent membrane proteins 1 (LMP1) and LMP2A are consistently expressed in NPC and can cooperate in bitransgenic mice expressed from the keratin-14 promoter to enhance carcinoma development in an epithelial chemical carcinogenesis model. In this study, LMP1 and LMP2A were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…LMP1 expression was detectable but notably lower than in the transfected or inducible models. Previous reports have shown that this level of LMP1 expression is comparable to those found in EBV-infected cell lines (39). Again, nanoparticle tracking analysis revealed an increase in vesicle secretion compared to that with control (empty pBabe vector) cells (P ϭ 0.026) (Fig.…”
Section: Resultssupporting
confidence: 59%
“…LMP1 expression was detectable but notably lower than in the transfected or inducible models. Previous reports have shown that this level of LMP1 expression is comparable to those found in EBV-infected cell lines (39). Again, nanoparticle tracking analysis revealed an increase in vesicle secretion compared to that with control (empty pBabe vector) cells (P ϭ 0.026) (Fig.…”
Section: Resultssupporting
confidence: 59%
“…Increased expression of other EBV lytic transcripts, BRLF1, BMRF1, and BLLF1, were also detected following expression of BZLF1. The BRLF1 is an immediate early transactivator activated by BZLF1, which plays an important role in lytic reactivation of EBV in infected epithelial cells [24]. The BMRF1 is an early EBV gene that encodes the polymerase accessory protein (EA-D), which is essential for lytic replication of EBV DNA.…”
Section: Reactivation Of Lytic Ebv Infection In C17 Cell Linementioning
confidence: 99%
“…A previous study has demonstrated a role for LMP1 in DNA repair suppression through the PI3K/AKT pathway and inactivation of FOXO3a and DDB1 (55). Coexpression of LMP1 and LMP2A in EBV-negative NPC cells is accompanied by a reduction in γH2AX phosphorylation in response to treatment with genotoxins, which can promote DNA replication stress or single-strand breaks (56). Furthermore, in EBV-infected B cells, EBNA3C was reported to suppress DNA damage repair responses (57,58).…”
Section: Discussionmentioning
confidence: 95%